Determinants of Effective Tax Investigations in Malaysia - Raig, J.; Pope, Jeffrey; Pinto, Dale (Thomson Brookers, 2014)
Whilst most tax authorities throughout the world publish their organisation’s objectives and policies, hitherto, there is very little research investigating the attitudes of those at the “front line”, namely tax investigation officers. This qualitative study investigates the attitudes of 16 senior investigation officers from the Inland Revenue Board Malaysia (IRBM) who are also the directors of investigation branches and divisions throughout the country. The sensitive area of criminal tax investigations as opposed to civil investigations is also examined in this article. An individual semi-structured interview method was used for this research. It is found that the effectiveness of tax investigations is strongly influenced by the professional proficiency of the officers, which incorporates their knowledge and skills, ability to work independently, high integrity as well as their capacity for being a good team worker. In addition, the other factors that were found to be influential include tax penalties and the enforcement strategies of the IRBM. The degree of tax law complexity, whilst important, was found to be relatively less important than the foregoing factors. Although this research was based on Malaysian officers’ experience, the study is placed in the context of international research, and uses Australian and Organisation for Economic Co-operation and Development (OECD) policies and recommendations as comparative reference points wherever possible.